Transient Two-Phase-Flow Model for Predicting Column Formation in Intermittent Gas Lift Systems - Sandoval, Sarita; Rojas-Solorzano, L.; Gasbarri, Sandro (One Petro, 2005)
The major objective of this work is to generate a mathematical model, allowing the prediction of mixture density, liquid holdup, the pressure gradient in the pipe and the real column size. This is useful for optimizing cycle times and the amount of gas required to lift the fluids and to improve the diagnostic and simulation software of IGL wells
Keywords: Research Subject Categories::TECHNOLOGY::Engineering mechanics; mechanical engineering